2018
DOI: 10.1016/j.compbiomed.2018.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Stacked classifiers for individualized prediction of glycemic control following initiation of metformin therapy in type 2 diabetes

Abstract: Objective: Metformin is the preferred first-line medication for management of type 2 diabetes and prediabetes. However, over a third of patients experience primary or secondary therapeutic failure. We developed machine learning models to predict which patients initially prescribed metformin will achieve and maintain control of their blood glucose after one year of therapy. Materials and Methods: We performed a retrospective analysis of administrative claims data for 12,147 commercially-insured adults and Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…Dennis H Murphree et al built several ML models to predict good HbA1c control (<7.0%) among T2D patients, which showed the potential for applying ML to solve problems in medical fields ( Tsao et al, 2018 ). Consistent with prior research studies ( Murphree et al, 2018 ; Tsao et al, 2018 ; Zarkogianni et al, 2018 ; Aminian et al, 2020 ), the findings of this study showed high AUCs.…”
Section: Discussionsupporting
confidence: 92%
“…Dennis H Murphree et al built several ML models to predict good HbA1c control (<7.0%) among T2D patients, which showed the potential for applying ML to solve problems in medical fields ( Tsao et al, 2018 ). Consistent with prior research studies ( Murphree et al, 2018 ; Tsao et al, 2018 ; Zarkogianni et al, 2018 ; Aminian et al, 2020 ), the findings of this study showed high AUCs.…”
Section: Discussionsupporting
confidence: 92%
“…While many patients need to start metformin at a lower dose and gradually increase it so as to minimize gastrointestinal side effects. 9 In conclusion, the results of the present study show that the efficacy of high-dose metformin is dose-dependent in Japanese patients with type 2 diabetes and the efficacy and safety of metformin were similar when taken either twice daily or three times daily. 10 There were 82 type 2 diabetes mellitus patients with prescribed 500 mg metformin twice daily.…”
Section: Discussionsupporting
confidence: 57%
“…ML models can provide valuable insights into the importance of dosage in the real-world use of drugs in the context of a multitude of demographic and clinical factors. For example, the critical importance of attaining target metformin dosage for optimal glycemic control could be demonstrated in a large reverse translational ML analysis of administrative claims data for 12,147 commercially insured adults and Medicare Advantage beneficiaries with prediabetes or diabetes in the context of 58 demographic, laboratory, and co-morbidity-related patient-specific factors ( 78 ). This analysis used an ensemble model incorporating diverse methods (e.g., RF, gradient boosting, regression splines, discriminant analysis) to allow patient-specific prediction of 1-year glycemic control for adult patients with either diabetes or prediabetes who are newly prescribed metformin.…”
Section: Dosementioning
confidence: 99%